Study of heat transfer and friction loss analysis of flowing fluid in different configuration of closed conduit flow / Puravi Saminathan - Puravi, Saminathan (2021)
The heat exchanger available on market satisfies the elementary conditions. However, there are very few research on difference shape and its efficiency on heat exchanger. With new design of shape of this study is intend to improve the efficiency of heat exchanger. A CFD package (ANSYS FLUENT) will be use for the numerical study of heat transfer and flow characteristics of a single pipe heat exchanger for annular flow, with 2 shape of pipe and the results then will be compared. The simulation will be carry out for water to water heat transfer characteristics and for same length and same diameter of tube and annulus and for same input temperature. Consequently this study concerned on nano fluid with different parameter which has the best heat transfer in circular and square tube. The heat transfer coefficient will be measured and has compared